Konsep Dhalal Dalam Al-Qur’an; Analisis Semantik - Ahmad Saddad (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This research aims to reveal the concept of dala>l in the Qur'an. The research method used was qualitative descriptive. The data were collected by library research documentation techniques. The data’s technical analysis was qur’anic semantic. The result showed that the basic meaning of dala>l is lost. While the relational meaning refers to several meanings: First, the meaning of heretical when accompanied by the words kufr, shirk, muna>fiq, za>lim, and fa>siq, accompanied by mubi>n, ba'i>d, and kabi>r, accompanied by the words shaita>n, and hawa>’. Second, it means confusion when turning up the righteous. Third, it means to forget when talking about the problem of witnessing. Dala>l has several equivalents of the words gayy, gaflah, zaig, tugya>n, and 'amhan, while the opponent is said to be huda>. The development of the meaning dala>l is reviewed from the synchronic- diachronic aspect pointing to three periods. The pre-Quranic period refers to conditions of loss, misfortune, and futility. The Qur'anic period carries the meaning dala>l pre-qur'anic to religious meaning. The post-Qur'anic period dala>l experienced a narrowing of meaning, namely, takfir and bid’ah.",